Purview of Fatwa from legal ruling to community building: case of Samasta in South India - Muhsin, Sayyed Mohamed (Mission Soft Foundation, 2022)
The predominant legal and political systems and the educational formation cause a great deal of impact on muftis (issuers of the fatwas) and their methodology of iftā’ (issuance of fatwa). Therefore, a methodical examination of the extensively accessible fatwa literature could expose the nuances of the Muslims' daily lives, priorities, level of their faith, and bothering issues during different periods of Islamic history. Based on the study of the interplay between fatwas and people’s responses to them, Samasta appears to be an instrumental religious authority in Kerala. The mentioned incidents and examples in this article, which are for illustration only, substantiate that, at times, the role of muftis is not limited to answering the Islamic questions. But, it has more profound implications in the religious and social textures of the community where Mufti operates.